Software Protection: A Comparative Study Between The UK And Malaysia Law - Abaei, Somayeh (2006)
Computer software copyright protection is inextricably linked to the structure of the new media facilitated by the internet access. The challenge is posed by the fast development of the internet, which now allows users instantaneous access to vast resources and digital repertoires that include copyright works.